Analisis Yuridis Putusan Majelis Hakim Pada Penyalahgunaan Narkotika - Firman Candra (Lembaga Marwah Rakyat, 2022)
A verdict by a panel of judges in a criminal case is a verdict from a panel of judges which is the final decision after a case goes through the trial process in a court of indictment, exception, response, interlocutory verdict, evidence, witnesses, charges, pledoi and finally the verdict at the court of first instance and contains sanctions and or fines for the Defendant. The decision of the panel of judges is compelling, meaning that if there is a party that does not comply, the judge can order the party concerned to comply with it with his own awareness or coercion. The judge's decision has legal consequences for the parties involved. Legal consequences are actions taken to obtain an effect the defendant wants and which is regulated by law. This action is called a legal action. So in other words, legal consequences are the result of a legal action, in the form of: the birth of a sanction due to an action that is against the law. In the case of narcotics abuse, there are many considerations made by the panel of judges because narcotics are already an extraordinary crime, such as corruption, serious human rights crimes and terrorism. Keywords: narcotics, the verdict of the panel of judges